A conserved element in the leader mediates post-meiotic translation as well as cytoplasmic polyadenylation of a Drosophila spermatocyte mRNA. - Schäfer, M (1990)
We have previously shown that Mst87F (previously called mst(3)g1-9), a gene which is exclusively expressed in the male germ line of Drosophila melanogaster, is subject to negative translational control. While transcription of this gene takes place premeiotically, translation occurs only after the elongation of spermatids is complete. We report here the identification of a sequence element within the first 45 nucleotides of the leader which is crucial for this translational regulation. Sequence comparison with six other genes, which form a gene family with Mst87F, shows the conservation of a twelve nucleotide element within this leader segment. It is found in all genes at positions +28 to +39 of the leader. Deletion of this element or alteration of two nucleotides by in vitro mutagenesis both lead to the breakdown of the translational control mechanism. The poly(A) tail of the Mst87F mRNA becomes longer and heterogeneous in length when the mRNA is recruited for translation. We present evidence that the control for this additional polyadenylation also resides within the conserved element of the leader.